EXACERBACIÓN APICAL POSTERIOR A TRATAMIENTO ENDODÓNTICO (2012)
An endodontic treatment generates high expectations for the patient due to the popular belief treatment be uncomfortable, painful, stressful it takes several sessions to complete it. When the pulp is symptomatic, these expectations rise and the professional expects to finish and to remove all the symptoms to ensure the success of therapy. Endodontic exacerbations are complications than can be presented during endodontic treatment to form periapical inflammatory processes that occur at the end of treatment. Some factors influence the development of these complications such as pulp diagnosis, the presence of sinus tracts, extensive instrumentation, lack of instrumentation and irrigation, among others. This article describes the case of a premolar with an initial diagnosis of chronic suppurative apical periodontitis, endodontic retreatment under which introduced an error in the preparation by subinstrumentation to determine a working length that caused insufficient and inadequate cleaning apical injury.